Land ownership succession in the agricultural frontier: The case of the Sierra Del Lacandón National park, Guatemala - Laurel SUTER; David LÓPEZ-CARR (European Journal of Geography)
This study investigates land ownership turnover in an area that is a priority conservation zone, the Sierra del Lacandón National Park (SLNP), Petén, Guatemala. Migration to Petén since the 1950s has eliminated 60% of Petén’s forests. We analyze panel-data consisting of household interviews conducted with subsistence farmers living in the SLNP or its buffer zone in 1998 and 2009: 247 household interviews in eight communities in 1998, and repeat interviews conducted in 2009 when present. In the intervening 11 years, there has been substantial consolidation and splintering of the 1998 farm parcels. Half of the landowning households in 1998 sold land by 2009. The most commonly cited reason for a household to sell its land is for payments related to a medical emergency or debt. Regression analysis suggests early adopters of cattle and higher value crops were less likely to have sold their land by 2009.